2005
DOI: 10.1083/jcb.200502062
|View full text |Cite
|
Sign up to set email alerts
|

Methyl CpG–binding proteins induce large-scale chromatin reorganization during terminal differentiation

Abstract: Pericentric heterochromatin plays an important role in epigenetic gene regulation. We show that pericentric heterochromatin aggregates during myogenic differentiation. This clustering leads to the formation of large chromocenters and correlates with increased levels of the methyl CpG–binding protein MeCP2 and pericentric DNA methylation. Ectopic expression of fluorescently tagged MeCP2 mimicked this effect, causing a dose-dependent clustering of chromocenters in the absence of differentiation. MeCP2-induced re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
264
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(282 citation statements)
references
References 60 publications
(85 reference statements)
16
264
2
Order By: Relevance
“…For example, the percentage estimate of spots (>1.5 µm diameter) per nucleus in ATRA-treated cells is: +/+, 1%; +/ic, 2%; ic/ic, 32%. Coalescence of centromeric heterochromatin has been previously described in terminally differentiating mouse myotube cells, [51] with evidence presented for central roles in the aggregation process due to increased levels of methylated DNA binding proteins, MeCP2 and MBD2, and of heterochromatic DNA methylation. However, no shift of the centromeric heterochromatin towards the nuclear envelope was reported.…”
Section: Discussionmentioning
confidence: 59%
“…For example, the percentage estimate of spots (>1.5 µm diameter) per nucleus in ATRA-treated cells is: +/+, 1%; +/ic, 2%; ic/ic, 32%. Coalescence of centromeric heterochromatin has been previously described in terminally differentiating mouse myotube cells, [51] with evidence presented for central roles in the aggregation process due to increased levels of methylated DNA binding proteins, MeCP2 and MBD2, and of heterochromatic DNA methylation. However, no shift of the centromeric heterochromatin towards the nuclear envelope was reported.…”
Section: Discussionmentioning
confidence: 59%
“…In accordance with our previously described results, we observed that 20% of treated cells showed an increase in nuclear size. 12 Western blotting analysis of untreated and treated human fibroblasts showed that BAF protein level did not change after treatment with prelamin A interfering drugs (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…GFP-BAF, 17 full-length FLAG-tagged rat prelamin A (LA-WT, pCI mammalian expression vector) and the mutated constructs LA-C661M, LA-L647R and LA-∆50 were transiently transfected into HEK293 cells using FuGene reagent (Roche). 9,12,23,44 Biochemical and immunofluorescence analyses were performed 24 hours after transfection. In human skin fibroblast cells the accumulation of different prelamin A intermediates were obtained using 25 µM mevinolin (Sigma), 10,12 or 20 µM 1-N-acetyl-S-farnesyl-Lcysteine methylester (AFCMe, Alexis).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the MBD-containing MBPs, the expression of MBD2 and MeCP2 is very low in proliferating myoblasts but increases during myogenic differentiation [40], suggesting that their main role is in terminal muscle differentiation. In support of this hypothesis, up-regulation of these two proteins leads to the reorganization of heterochromatin, and contributes to the terminal differentiation of myotubes [40]. Upon oxidative stress induction, the nuclear translocation of focal adhesion kinase and its consequent interaction with MBD2 have been reported to induce skeletal muscle differentiation [41].…”
Section: Discussionmentioning
confidence: 99%